Neck management in metastatic cutaneous squamous cell carcinoma of the head and neck - Xu, Ning; Sun, Qiang (Frontiers in Oncology, 2024)
Objective: Optimal neck management remains unclear in head and neck cutaneous squamous cell carcinoma (HNcSCC) with parotid metastasis, our goal was to compare the impact of different cervical treatments in HNcSCC with parotid metastasis. Methods: Patients were retrospectively included. Primary outcome variables were regional control (RC) and disease specific survival (DSS). Impact of observation, elective neck irradiation (ENI), and elective neck dissection (END) was analyzed using Cox model with presentation via hazard ratio (HR) and 95% confident interval (CI). Results: In total, 268 patients were enrolled. In Cox model for RC, compared with ENI, observation was associated with a significantly higher risk of regional recurrence (p=0.001, HR: 2.50, 95%CI: 1.45-4.30). However, END showed a comparable influence on regional recurrence (p=0.246, HR: 0.70, 95%CI: 0.38-1.28). In Cox model for DSS, END demonstrated a similar HR of 0.62 (95%CI: 0.30-1.26) compared to ENI (p=0.184). However, patients who underwent observation were associated with an additional nearly two-fold risk of cancer-related mortality (HR: 2.85, 95%CI: 1.55-5.23). Subgroup analysis showed ENI predicted comparable RC (p=0.389) and DSS (p=0.346) in patients with 1 or 2 metastatic parotid lymph nodes, but worse RC (p=0.007) and DSS (p=0.024) in patients with 3+ positive lymph nodes.In HNcSCC with parotid metastasis, elective treatment of neck lymph nodes by END or ENI should be always performed.